City on a hill. Season one [videorecording (DVD)] - MacLean, Chuck (Paramount : Showtime, 2019)
Set in 1990s Boston, an assistant district attorney and a corrupt yet venerated FBI veteran work together to take on a case that grows to involve, and ultimately subvert, the entire criminal justice system of Boston. Family, blood, betrayal, honor, corruption, all combine in this powerful series that's one-part gritty thriller and another intimate family drama.